2011
DOI: 10.1590/s1517-83822011000400033
|View full text |Cite
|
Sign up to set email alerts
|

Growth and exopolysaccharide production by Streptococcus thermophilus ST1 in skim milk

Abstract: To analyze the exopolysaccharide (EPS) production by Streptococcus thermophilus ST1, cultures were cultivated in 10% (w/v) reconstituted skim milk under different growth conditions including various temperatures and pHs of growth medium, supplementation of the medium with various carbon sources (glucose, lactose, sucrose, galactose and fructose) and nitrogen source (whey protein concentrate, or WPC).The results showed that most EPS production by strain ST1 was obtained at a temperature (42°C) and pH (6.5) opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 36 publications
2
39
0
6
Order By: Relevance
“…Leo et al, 2007 indicated that Lactobacillus fermentum TDS030603 is able to produce more EPS at 37 than at 40°C. On the other hand, the growth and exopolysaccharide (EPS) production by Lactobacillus fermentum F6 increased to a maximum value of 44.49 mg/l of EPS at 37°C (Zhang et al, 2011). d.…”
Section: Optimization Of Production Of Epsmentioning
confidence: 98%
“…Leo et al, 2007 indicated that Lactobacillus fermentum TDS030603 is able to produce more EPS at 37 than at 40°C. On the other hand, the growth and exopolysaccharide (EPS) production by Lactobacillus fermentum F6 increased to a maximum value of 44.49 mg/l of EPS at 37°C (Zhang et al, 2011). d.…”
Section: Optimization Of Production Of Epsmentioning
confidence: 98%
“…Homopolysaccharides can be introduced in sourdough products, influencing the structural quality and backing ability in bakery products, while heteropolysaccharides are used as food additives in dairy products [154]. EPS contribute to the organoleptic quality of the fermented foods, in texture, taste perception, mouth-feel and stability [153,155]. The above researchers reported that there is no information about the effects of bacterial EPS in nondairy foods, such as meat products, sauerkraut and vinegar.…”
Section: Definition and Classification Of Exopolysaccharidesmentioning
confidence: 99%
“…The above researchers reported that there is no information about the effects of bacterial EPS in nondairy foods, such as meat products, sauerkraut and vinegar. Although EPS are tasteless, they prolong the time that the milk product spends in the mouth, enhancing its delicacy through an improved volatilization of the intrinsic flavors [153,155].…”
Section: Definition and Classification Of Exopolysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations